2015
DOI: 10.1631/jzus.b1400337
|View full text |Cite
|
Sign up to set email alerts
|

Leucine and histidine independently regulate milk protein synthesis in bovine mammary epithelial cells via mTOR signaling pathway

Abstract: Abstract:The aim of this study is to investigate the effects of leucine (Leu) and histidine (His) on the expression of both the mammalian target of rapamycin (mTOR) signaling pathway-related proteins and caseins in immortalized bovine mammary epithelial cells (CMEC-H), using a single supplement through Western blotting. The Earle's balanced salt solution (EBSS) was set as the control group and other treatment groups, based on the EBSS, were added with different concentrations of Leu or His, respectively. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 45 publications
12
51
0
Order By: Relevance
“…Leu increased CSN1S1, CSN2, and CSN3 abundance in BMECs (Gao et al, 2015). Leu increased CSN1S1, CSN2, and CSN3 abundance in BMECs (Gao et al, 2015).…”
Section: Effect Of Leu On Milk Protein Synthesismentioning
confidence: 90%
See 2 more Smart Citations
“…Leu increased CSN1S1, CSN2, and CSN3 abundance in BMECs (Gao et al, 2015). Leu increased CSN1S1, CSN2, and CSN3 abundance in BMECs (Gao et al, 2015).…”
Section: Effect Of Leu On Milk Protein Synthesismentioning
confidence: 90%
“…At present, the effect of AA on milk protein synthesis was widely demonstrated. Leu increased CSN1S1, CSN2, and CSN3 abundance in BMECs (Gao et al, 2015). Liu et al (2012) reported that the supplement of Leu significantly increases the expression of STAT5A and STAT5 has a positive effect on the expression of CSN2.…”
Section: Effect Of Leu On Milk Protein Synthesismentioning
confidence: 94%
See 1 more Smart Citation
“…The production of milk, protein, casein and lactose were significantly higher following histidine supplementation (2.5 g/L in water for drinking or diet supplemented with 13.6 g/d) compared to control (Doelman et al, 2008;Hadrov a et al, 2012). Gao et al (2015) investigated the effects of leucine and histidine on the mammalian target of rapamycin (mTOR) signalling pathway in milk protein synthesis using CMEC-H (bovine mammary epithelial cells) and demonstrated that leucine or histidine stimulated the expression of different forms of caseins.…”
Section: Safety For the Target Speciesmentioning
confidence: 93%
“…Compared with 17% crude protein (CP) group and 20% CP group, the 14% CP group presented the lowest average daily feed intake (ADFI) and average daily gain (ADG), as well as the expression of ASCT2, 4F2hc, and ATB 0 mRNA in the jejunum, indicating that a 14% CP diet supplemented with crystalline amino acid (AA) may not transport enough AA into the body to maintain growth performance in piglets. Gao et al (2015) demonstrated that L-leucine and L-histidine supplementation in medium both can upregulate milk proteins, such as α-casein, β-casein, and κ-casein synthesis via the activation of mammalian target of rapamycin (mTOR) pathway in bovine mammary epithelial cells. Nie C.X.…”
Section: In This Issuementioning
confidence: 99%